Students’ assessments in learning programming based on bloom’s taxonomy / Rozita Kadar ... [et al.] - Kadar, Rozita; Mohamed Yusoff, Syarifah Adilah; Warris, Saiful Nizam; Abu Bakar, Mohd Saifulnizam (UiTM Cawangan Perlis, 2021)
Learning a program is important for all students, not only students from the field of computer science but all fields. Programming languages are different from human communication languages as they have different structural forms. This makes it difficult for beginners especially for non-computer science students to understand the structure of programming languages. Therefore, to learn and understand the programming language more effectively, this article focuses on the important structure in learning a program from the initial stage to the advanced level suitable for non-computer science students. The objective of this article is to suggest important elements that can be assessed on these students which are to measure their understanding as they learn programming languages. The questions proposed to measure students' understanding were based on Bloom's Taxonomy, which covers six levels of understanding. It is hoped that this assessment proposal can act as a guideline for educators in fully focusing on important matters during the teaching and learning process.